ASSOCIATION BETWEEN SEVERITY AND DEPRESSION IN PARKINSON’S PATIENTS - Popy Paramitha, Aida Fithrie & Haflin Soraya Hutagalung (International Journal of Research Science and Management, 2020)
Background: Parkinson disease (PD) has motor manifestations namely resting tremor, rigidity, bradykinesia and postural instability. In addition, non-motor symptoms such as psychiatric symptoms such as depression, anxiety, hallucinations, psychosis, delusions and sleep. Accompanying depression is the most common nonmotor symptom in Parkinson's. Depression in Parkinson's occurs in about 40% of patients and on average there is major depression and minor depression. Objective: To determine the relationship of severity with depression in Parkinson's patients. Method: This study used a cross sectional design. Sampling was conducted at H. Adam Malik General Hospital Medan and network hospital. The study sample was taken as many as 25 subjects consecutively, with primary data sources obtained from all patients who had been diagnosed with Parkinson's disease based on the UKPD Society Bank's Clinical Criteria for Probable Parkinson's Disease criteria. Data analysis using the Spearman correlation test. Results: The demographic characteristics of the study subjects were 19 (76%) men and 6 people (24%) women, with the oldest age being 77 years and the youngest 49 years, mean age was 61.52 ± 6.97 years. The majority of the patients are senior high school, self-employed, and the Batak ethnic group. There is a significant relationship between the MDS-UPDRS subscale and the level of depression in Parkinson's patients with a p value <0.05. Conclusion: There is a significant relationship between severity and depression in Parkinson's patients.